Podnikatelský záměr rozvoje firmy - Vaněček, Milan (Vysoké učení technické v Brně. Fakulta podnikatelská, 2019)
Tato diplomová práce se zabývá analýzou současného obecného a oborového okolí a vnitřního stavu společnosti STROJÍRNA OSLAVANY, spol. s r. o. Na základě zjištěných informací obsahuje zpracovaný návrh firemní strategie, která by měla pomoci upevnit pozici firmy na trhu a zajistit její další rozvoj .

This Master’s thesis deals with the analysis of the existing, general and departmental environment and internal status of the company STROJÍRNA OSLAVANY, spol. s r. o. On the basis of the finding informations the work includes the processed suggestion of the corporate strategy, which should be helpful to establish the company position on the market and assure her additional development.
Entrepreneurial Intention of Business development
Keywords: Firemní strategie Rozvoj podniku Prodejní analýza Finanční analýza Rentabilita Finanční zdraví Konkurenční výhoda Cíle společnosti; Corporate strategy Company development Sales analysis Financial analysis Profitability Financial health Competitive advantage Company objectives